Analysis OfMachine Learning Models For Cloud Network Analytics InDynamic Autoselection And Autotuning - Dr. G. Apparao Naidu, Dr. P. SrinivasaRao, B. Nageswara Rao, K. Archana (International Journal of Advanced Science and Technology, 2020)
The complex and distributed data of the cloud network monitoring. Cloud monitoring signals may appear, go away or change their importancewith time, and consistency. Therefore, modeling for machine learning used in a particular data set is soon insufficient. A sample at some stage may be extremely accurate, however, because of changes in input data and operations it may then lose its accuracy. Therefore, dynamic model selection also involves distributed learning. Models with low performance (but aggressively tuned for the preceding data) will be removed in this range when new or stand-by models are added.We propose a new cloud methodology in this paperSelection and tuning for automatic ML models, automating and competing with existing methods building and selecting models.Before creating targeted supervised learning models, we employ unattended learning towardwelldiscover data spaceAutomatic fashion. Automatic fashion. We particularly build the auto tuning and container-orchestration Cloud DevOps architecture.and messaging between containers to dynamically create and evaluate instantiations using a new autoscaling techniquethe algorithms of ML. On cloud safety data sets the proposed approach and tool are shown.